The Characteristics of the Morphological Genotypes of Local Sorghum [Sorghum bicolor (L.) Moench] from Buton Selatan - Agus Slamet; Hisra Hisra; Rajab Rajab (Scientiae Educatia: Jurnal Pendidikan Sains, 2020)
Local sorghum (Sorghum bicolor) is a cereal crop that the people of Bahari Village, Buton Selatan Regency still cultivate as an interlude crop of corn. Local sorghum (Sorghum bicolor) functions as genetic material and a gene donor to improve the crop’s characters in a plant breeding program. Therefore, it is necessary to take conservation steps to maintain the availability of sorghum germplasm collections. This study aims to characterize local sorghum (Sorghum bicolor) from Bahari Village, Buton Selatan Regency based on morphological characters (qualitative vegetative and generative parameters) and agronomic characters. This study was an explorative study that directly identified the genotypes of local Sorghum bicolor cultivated in the field. This study reveals six genotypes of local Sorghum bicolor; they are Labanda, Lapandewa, Lagadi, Wapinauri, Mbae, and Madea. The differences in sorghum genotypes can be more clearly identified in the generative phases, namely the symmetrical and pyramidal panicle shapes; the panicle density can be grouped into loose, slightly compact, and compact; husk colors vary from black, orange, grey, yellow, white, to red; the husk traits are categorized into short, slightly long, and very long; and the seeds are categorized round and round flat and white and brown. Meanwhile, the agronomic characters indicate that sorghum genotypes have long panicles; the weight of 100 seeds vary in categories from very low, low, to moderate; and one sorghum genotype (genotype Lagadi) has the fastest flowering and harvest ages than the other genotypes.